Finance at Your Fingertips: How Mobile Apps Shape Decisions - Rodriguez Diez, Ernesto; Sesé, Francisco Javier; Mínguez, Ana (Jornada de Jóvenes Investigadores del I3A, 2025)
This study analyzes how mobile applications influence financial decision-making. Using data from 50,000 clients of a Spanish bank, it was found that those who use the app are less likely to incur delinquency (β = –1.110) and, for the most part, are also less likely to experience overdrafts (β = –0.122).